Studi Efektifitas Indikator Kestabilan Tegangan Pada Model Dinamis Sistem Tenaga Listrik - Muhammad Nizam (Semesta Teknika, 2006)
The paper presents the effectiveness of voltage stability indices for dynamic power system modelling study in providing information about the proximity of voltage collapse in power system. Four simple stability indices as Voltage Instability Predictor (VIP), Impedance Stability Index (ISI), Line Index (L index) and Voltage Collapse Prediction Index (VCPI) are compared using WSCC 9 bus test system. The comparison show the ISI and VCPI are much more reliable indicator, give the fast indication and fast time computation than L index for voltage collapse in dynamics voltage collapse prediction.